Absence of toxicity of strobilanthes crispaJuice in acute oral toxicity study in sprague dawley rats - Norfarizan-Hanoon, N.A; Asmah, R; Fauziah, O; Rokiah, M.Y; Faridah, H (Universiti Kebangsaan Malaysia, 2012)
This study evaluated four different doses of Strobilanthes crispa juice (700, 2100, 3500 and 4900 mg kg-1 of body weight) administered orally to normal female and male Sprague dawley rats on possible changes in various physical, behaviour, morphology and biochemical parameter. The rats were treated with a single dose of juice and observed for 14 days. No significant toxicity was observed with respect to clinical parameters and organ morphology. In addition, no significant changes were observed in the level of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, creatinine and albumin. The S. crispus juice was found to be safe at the maximum dose used in this study (4900 mg kg-1 of body weight).